The causal effect of adipose tissue on Hodgkin’s lymphoma: two-sample Mendelian randomization study and validation - Wu, Lihua; Liao, Fei; Guo, Xiangli; Li, Nainong (Frontiers in Immunology, 2024)
Background Extensive research has been conducted on the correlation between adipose tissue and the risk of malignant lymphoma. Despite numerous observational studies exploring this connection, uncertainty remains regarding a causal relationship between adipose tissue and malignant lymphoma. Methods The increase or decrease in adipose tissue was represented by the height of BMI. The BMI and malignant lymphoma genome-wide association studies (GWAS) used a summary dataset from the OPEN GWAS website. Single-nucleotide polymorphisms (SNPs) that met the criteria of P <5e–8 and LD of r2 = 0.001 in the BMI GWAS were chosen as genetic instrumental variants (IVs). Proxy SNPs with LD of r2 > 0.8 were identified, while palindromic and outlier SNPs were excluded. Mendelian randomization (MR) analysis used five methods, including inverse-variance weighted (IVW) model, weighted median (WM), MR-Egger, simple mode, and weighted mode. Sensitivity assessments included Cochran’s Q test, MR-Egger intercept test, and leave-one-out analysis. Participants randomly selected by the National Center for Health Statistics (NHANSE) and newly diagnosed HL patients at Fujian Medical University Union Hospital were used for external validation. Results The results of the MR analysis strongly supported the causal link between BMI and Hodgkin’s lymphoma (HL). The research demonstrated that individuals with lower BMI face a significantly increased risk of developing HL, with a 91.65% higher risk (ORIVW = 0.0835, 95% CI 0.0147 – 0.4733, P = 0.005). No signs of horizontal or directional pleiotropy were observed in the MR studies. The validation results aligned with the results from the MR analysis (OR = 0.871, 95% CI 0.826 – 0.918, P< 0.001). And there was no causal relationship between BMI and non-Hodgkin’s lymphoma (NHL). Conclusions The MR analysis study demonstrated a direct correlation between lower BMI and HL. This suggested that a decrease in adipose tissue increases the risk of developing HL. Nevertheless, further research is essential to grasp the underlying mechanism of this causal association comprehensively.